Symptomatic improvement after mesh removal: a prospective longitudinal study of women with urogynaecological mesh complications. (27th June 2021) - Pace, N; Artsen, A; Baranski, L; Palcsey, S; Durst, R; Meyn, L; Moalli, PA
Abstract : Objective: To compare clinical characteristics and outcomes in patients undergoing excision of polypropylene urogynaecological mesh for pain, mesh exposure or both. Design: Prospective, longitudinal cohort. Setting: Academic tertiary referral centre. Population: Women undergoing complete vaginal mesh excision for mesh exposure and/or pain. Methods: Clinical and patient‐reported outcomes assessing pain (visual analog scale, VAS), bother (Pelvic Floor Distress Inventory, PFDI) and functional impact (Pelvic Functional Impact Questionnaire, PFIQ) were collected at baseline, 6, 12 and 24 months after complete mesh excision. Outcomes were compared by mesh type (sling, prolapse [transvaginal or sacrocolpopexy mesh], both) and complication (pain, exposure, both). Main outcome measures: 'Much better' or 'Very much better' on Patient Global Impression of Improvement (PGI‐I) up to 2 years after removal. Results: Of 173 women, 48 underwent removal for pain, 27 for exposure and 98 for exposure plus pain. 'Moderate to severe' baseline symptoms were reported by 75%; the most prevalent and severe symptom was dyspareunia. Patients with pain alone were most bothered (PFDI median 234.2, interquartile range 83, P = 0.02) and had the highest functional impact (PFIQ median 181, interquartile range 138, P < 0.001). After excision, only 33.3% of women with pain alone reported 'improved' symptoms (PGI‐I), versus 73.9% with exposure, 58.3% with exposure plus pain ( P = 0.03) with no differences in PGI‐I by mesh type. VAS scores decreased in all groups, but PFDI and PFIQ did not improve in pain patients. Conclusions: In women experiencing a pain complication after urogynaecological mesh insertion, mesh removal often does not improve symptoms. Tweetable abstract: Only 33% of women with pain complications have improved symptoms after urogynaecological mesh removal. Tweetable abstract: Only 33% of women with pain complications have improved symptoms after urogynaecological mesh removal.